Abraham versus Jacob - Lemański, Janusz (Collectanea Theologica, 2021)
This article deals with the formation process of the traditions concerning the three patriarchs from the book of Genesis. It can already be stated that the traditions of Abraham, Isaac, and Jacob were initially formed independently of one other. The chronological priority should be assigned to the tradition of Jacob. It was originally combined with the tradition of Isaac (in Amos), and before the exile it constituted the earliest point of reference for the search of roots and identity. It was only towards the end of the exile that the particular time and situation resulted in the local, Judaean traditions of Abraham starting to play a greater role also in the theological aspect. Abraham became then not only a model of faith, and an example of behaviour for the exiles and the repatriates, but also the first link in the chain of the three patriarchs. Some motifs in the story of Abraham may have been at that time borrowed from the traditions of Isaac (cf. Gen 26).